WP 5: Scaling innovation and digital tools for climate resilient food value chains - Baum, Michael; Anarbekov, Oyture; Lahham, Nisreen; Brouziyne, Youssef; Grosjean, Godefroy; Akramkhanov, Akmal; Abay, Kibrom A.; Govind, Ajit (International Center for Agricultural Research in the Dry Areas, 2022)
From Fragility to Resilience in Central and West Asia and North Africa (F2R CWANA) WP 5: Scaling innovation and digital tools for climate resilient food value chains Inception Workshop Morocco May 17, 2022